Decarbonizing German Family Firms - Friedl, Gunther; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2025)
In this Open Access Publication, we present four chapters that provide a holistic view of the critical steps in a family firm$1 (Bs decarbonization journey. Achieving the EU's climate targets relies heavily on German family firms, given their pivotal role in the economy and substantial greenhouse gas (GHG) emissions. First, we explore the measurement and accounting mechanisms of GHG emissions, leveraging data from German family firms across various industries. Second, we examine the management of goal tensions between environmental and economic objectives, focusing on how family firms can derive value from their emissions data. Third, with the upcoming Corporate Sustainability Reporting Directive (CSRD) and the importance of communicating decarbonization efforts to stakeholders, we analyze the implications of this reporting mandate for family firms. Fourth, given the high investment demands of decarbonization measures, profitability remains a critical concern. Therefore, we also delve into the relationship between corporate environmental performance and corporate financial performance, highlighting the intersection of sustainability and long-term financial viability. The Editor Gunther Friedl is professor of Business Administration and Management Accounting, head of the department of Management Accounting and dean of TUM School of Management.s
- Measurement and Accounting of Greenhouse Gas Emissions -- Management of Goal Tensions in Strategic Decision-Making -- Reporting of Sustainability Information under the CSRD -- Assessment of Financial Performance of Decarbonization.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Strategic planning; Leadership; Accounting; Business Strategy and Leadership; Accounting